Interaction between adenosine A2A receptors and cannabinoid CB1 receptors at the hippocampus : consequences for memory and plasticity - Mouro, Francisco Melo Albuquerque Saraiva, 1988- (2018)
Tese de doutoramento, Ciências Biomédicas (Neurociências), Universidade de Lisboa, Faculdade de Medicina, 2018